Mitigating Security Threats in the Sharing of Medical Data: A Comprehensive Review - Sekharan, Akhil; P.P., Joby; V.M., Praseetha (Law, State and Telecommunications Review, 2025)
[Purpose] The medical field is one of the most regular targets of cybersecurity assaults, which occur extensively worldwide. Medical data security is of extreme importance. Medical data, often stored electronically, faces frequent attacks from both internal and external sources during transmission and storage. Data breaches are an important concern in the healthcare industry. Attackers may target medical data for financial gain or identity theft. Even a single breach can expose sensitive patient information. [Methodology/approach/design] Cybersecurity measures are critical for safeguarding patient information and maintaining the integrity of healthcare applications in an increasingly digital healthcare landscape. [Findings] Legal software systems with updated software are essential, along with ensuring that the medical data is only accessible to authorised persons. [Practical implications] This paper explores the areas of cybersecurity relevant to healthcare applications, emphasizing the risks posed by well-known threats such as WannaCry, Medjack, NotPetya, and brainjacking.